2018
DOI: 10.3390/chemengineering2030042
|View full text |Cite
|
Sign up to set email alerts
|

Solar Fuels by Heterogeneous Photocatalysis: From Understanding Chemical Bases to Process Development

Abstract: The development of sustainable yet efficient technologies to store solar light into high energy molecules, such as hydrocarbons and hydrogen, is a pivotal challenge in 21st century society. In the field of photocatalysis, a wide variety of chemical routes can be pursued to obtain solar fuels but the two most promising are carbon dioxide photoreduction and photoreforming of biomass-derived substrates. Despite their great potentialities, these technologies still need to be improved to represent a reliable altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 260 publications
(371 reference statements)
0
9
0
Order By: Relevance
“…MATLAB was used to estimate: the tted coefficient values; determine the p-values and plot the models and data. The experimental design results were used to t the polynomial function shown by (2).…”
Section: Design Of Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…MATLAB was used to estimate: the tted coefficient values; determine the p-values and plot the models and data. The experimental design results were used to t the polynomial function shown by (2).…”
Section: Design Of Experimentsmentioning
confidence: 99%
“…1 However, major optimization in photocatalyst design is required for its applicability. 2 Possible approaches in heterogeneous photocatalysis to improve photocatalytic activity include photocatalyst dispersion on highly porous substrates and the use of coupling two semiconductors as photocatalysts. For these reasons, composite mixtures of ZnO and TiO 2 were prepared on an ordered mesoporous SBA-15 silica support for CO 2 photoreduction.…”
Section: Introductionmentioning
confidence: 99%
“…However, the higher activity of heterobimetallic systems with respect to monometallic ones have been reported mainly in the case in which one is a noble metal, as a result of a synergistic electronic effect [23]. At the moment, no wholly non-noble heterobimetallic systems have been reported for photoreforming processes [23,30]. Moreover, this transition metal selection can be more cost effective with respect to noble metal promoted catalysts and can possibly produce catalysts more active than the corresponding monometallic ones, as reported for Cu-Ni heterobimetallic systems, proving more active in steam reforming processes [31].…”
Section: Introductionmentioning
confidence: 99%
“…Material engineering aside, reactor design and catalytic conditions for CO2 photoreduction still need to be further investigated and standardised to compare materials photoactivity significantly. A wide variety of photocatalytic reactors has been reported [25,26,27], but due to a lack in standardisation in experimental procedures, reaction regimes and data collection and processing, it is difficult to compare results reported from different systems. Recently, gas phase systems have been preferred to liquid phase to overcome limitations by photon and mass transfer [27,28,29], focusing on gas phase systems operating at room temperature and atmospheric pressure [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of photocatalytic reactors has been reported [25,26,27], but due to a lack in standardisation in experimental procedures, reaction regimes and data collection and processing, it is difficult to compare results reported from different systems. Recently, gas phase systems have been preferred to liquid phase to overcome limitations by photon and mass transfer [27,28,29], focusing on gas phase systems operating at room temperature and atmospheric pressure [30][31][32]. A recent study reported that when reagents are in gas phase, CO2 undergoes deoxygenation faster than hydrogenation, improving selectivity to methane (CH4), which is the most desired solar fuel, due to its high hydrogen to carbon ratio [28].…”
Section: Introductionmentioning
confidence: 99%